SNO KARST: A French Network of Observatories for the Multidisciplinary Study of Critical Zone Processes in Karst Watersheds and Aquifers. Issue 1 (20th December 2018) - Jourde, H.; Massei, N.; Mazzilli, N.; Binet, S.; Batiot-Guilhe, C.; Labat, D.; Steinmann, M.; Bailly-Comte, V.; Seidel, J.L.; Arfib, B.; Charlier, J.B.; Guinot, V.; et al.
Abstract : Core Ideas: SNO KARST is dedicated to the study of karst functioning. Hydrodynamics and geochemistry are measured at springs and in karst compartments. Process sampling was set up at nine sites in various climatic contexts. Continuous monitoring concerns timescales from 10 to >50 yr. New tools and findings are due to the complementarity of gathered data. Karst aquifers and watersheds represent a major source of drinking water around the world. They are also known as complex and often highly vulnerable hydrosystems due to strong surface–groundwater interactions. Improving the understanding of karst functioning is thus a major issue for the efficient management of karst groundwater resources. A comprehensive understanding of the various processes can be achieved only by studying karst systems across a wide range of spatiotemporal scales under different geological, geomorphological, climatic, and soil cover settings. The objective of the French Karst National Observatory Service (SNO KARST) is to supply the international scientific community with appropriate data and tools, with the ambition of (i) facilitating the collection of long‐term observations of hydrogeochemical variables in karst, and (ii) promoting knowledge sharing and developing cross‐disciplinary research on karst. This paper provides an overview of the monitoring sites and collective achievements, such as the KarstMod modular modeling platform and the PaPRIKa toolbox, of SNO KARST. It also presents the research questions addressed within the framework of this network, along with major research results regarding (i) the hydrological response of karst to climate and anthropogenic changes, (ii) the influence of karst on geochemical balance of watersheds in the critical zone, and (iii) the relationships between the structure and hydrological functioning of karst aquifers and watersheds.